Impact of Fertiliser Amendment on Biomass Production of Bothriochloa pertusa Sown on a Coal Mine Spoil - Singh, Arvind (Indian Forester, 2007)
The impact of fertiliser amendment was studied on biomass production of grass Bothriochloa pertusa sown on a coal mine spoil. Two different doses of NPK fertiliser amendments were used along with control. The response to fertilisation was comparatively greater for shoot biomass than root biomass. The shoot biomass, root biomass and total biomass was significantly greater in fertilised plots compared to control plots. The root/shoot ratio was significantly greater in control than fertiliser amended plots.